Dynamic changes in ultrastructure of the primary cilium in migrating neuroblasts in the postnatal brain - Matsumoto, Mami; Sawada, Masato; García-González, Diego; Herranz-Pérez, Vicente; Ogino, Takashi; Nguyen, Huy Bang; Thai, Truc Quynh; Narita, Keishi; Kumamoto, Natsuko; Ugawa, Shinya; Saito, Yumiko; Takeda, Sen; et al. (The journal of neuroscience, 2019)
New neurons, referred to as neuroblasts, are continuously generated in the ventricular-subventricular zone of the brain throughout an animal's life. These neuroblasts are characterized by their unique potential for proliferation, formation of chain-like cell aggregates, and long-distance and high-speed migration through the rostral migratory stream (RMS) toward the olfactory bulb (OB), where they decelerate and differentiate into mature interneurons. The dynamic changes of ultrastructural features in postnatal-born neuroblasts during migration are not yet fully understood. Here we report the presence of a primary cilium, and its ultrastructural morphology and spatiotemporal dynamics, in migrating neuroblasts in the postnatal RMS and OB. The primary cilium was observed in migrating neuroblasts in the postnatal RMS and OB in male and female mice and zebrafish, and a male rhesus monkey. Inhibition of intraflagellar transport molecules in migrating neuroblasts impaired their ciliogenesis and rostral migration toward the OB. Serial section transmission electron microscopy revealed that each migrating neuroblast possesses either a pair of centrioles or a basal body with an immature or mature primary cilium. Using immunohistochemistry, live imaging, and serial block-face scanning electron microscopy, we demonstrate that the localization and orientation of the primary cilium are altered depending on the mitotic state, saltatory migration, and deceleration of neuroblasts. Together, our results highlight a close mutual relationship between spatiotemporal regulation of the primary cilium and efficient chain migration of neuroblasts in the postnatal brain. - SIGNIFICANCE STATEMENT Immature neurons (neuroblasts) generated in the postnatal brain have a mitotic potential and migrate in chain-like cell aggregates toward the olfactory bulb. Here we report that migrating neuroblasts possess a tiny cellular protrusion called a primary cilium. Immunohistochemical studies with zebrafish, mouse, and monkey brains suggest that the presence of the primary cilium in migrating neuroblasts is evolutionarily conserved. Ciliogenesis in migrating neuroblasts in the rostral migratory stream is suppressed during mitosis and promoted after cell cycle exit. Moreover, live imaging and 3D electron microscopy revealed that ciliary localization and orientation change during saltatory movement of neuroblasts. Our results reveal highly organized dynamics in maturation and positioning of the primary cilium during neuroblast migration that underlie saltatory movement of postnatal-born neuroblasts.